Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Numbered Head Together Di Sekolah Dasar - Velira Agustin Pratiwi; Mansurdin Mansurdin (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The aim of this research was to decribe the increasing of students achievement integrated thematic learning by using cooperative learning type Numbered Head Together. This reasearch was descriptive qualitative dan used quantitatif approach. This type of research was an action research. The subject of the research was the teacher and the students which consisted 18 students in grade V at SDN 32 Lubuk Alung. The result showed an increase in a) RPP observation for the first cycle was 75% (C), and the second cycle was 89% (A); b)  The result for the evaluation of teachers at the first cycle was 74% (C), the second cycle was 97% (A); c) the result for the evaluation of students at the first cycle was 74% (C), the second cycle was 97% (A); d) learning outcomes in the first cycle was 61% (C), and the second cycle was 89% (A).Key word: